The Effect of Using the Think Pair Share Model Toward Students’ Mathematic Communication Ability Derived from Their Leaning Motivation - Muhammad Abdi; Zulkifli Nelson; Hasanuddin (Journal of Research on Mathematics Instruction (JRMI), 2021)
This study to investigate whether there are differences in mathematical communication skills between students who take Think Pair Share learning and students who follow conventional learning when viewed from the learning motivation of students at SMP Negeri 4 Tambang. This study is a quasi-experimental study that aims to investigate a causal relationship by giving treatment to one class and comparing the results with one class that is given a different treatment. The subjects in this study were students of class VIII-G and class VIII-E of SMP Negeri 4 Tambang and the object of this research was the influence of the application of the Think Pair Share learning model on students' mathematical communication skills in terms of learning motivation. The data analysis technique used by the researcher is t-test, correlation (Product Moment), and two-way ANOVA. The instrument used is a description test to measure students' mathematical communication skills, and a questionnaire to measure the level of student motivation. Based on the results of the study, it was concluded that (1) there were differences in communication skills between students using the Think Pair Share learning model and students using conventional learning models (2) there were differences in student motivation in the experimental class and the control class (3) there was a contribution between learning motivation and metamatic communication. . (4) there is no interaction between the learning model and student motivation on students' mathematical communication skills. Thus, in general, the Think Pair Share learning model has an effect on mathematical communication in terms of student motivation at SMP Negeri 4 Tambang..